Geology of the central and southern domains of the Koras Group, northern Cape Province - Sanderson-Damstra, Christopher Gerald (Rhodes University, Faculty of Science, Department of Geology, 1983)
The Central and Southern Domains of the Koras Group, situated on the Doornberg Lineament, are the structurally preserved remnants of a once more widespread late-syntectonic cover sequence. Detailed examination of the field relationships, lithology and petrography together with new geochemical data (30 analyses) has resulted in the proposal of a new geological succession consisting mainly of two cycles of bimodal basaltic-rhyolitic volcanics with interbedded, immature conglomerates and lithic greywackes. These two cycles, named the Boomrivier and Leeudraai Formations, are overlain by the immature, polymictic orthoconglomerates and red arkosic sandstones of the Kalkpunt Formation. The first volcanic cycle commenced with the Lambrechtsdrif basaltic andesites and was followed, after a short hiatus, by the Swartkopsleegte rhyodacites. The second cycle comprises the Rouxville basalts and basaltic andesites and the Swartkop and Kenilworth rhyolites. Field evidence suggests that eruption of the rhyolitic and basaltic volcanics in the second cycle was contemporaneous. Geochemically, the volcanics can be classified as an "average-K" to high-K, tholeiitic, subalkaline association which exhibits general similarities to other Southern African bimodal associations e.g., the tholeiitic lavas of the Wilgenhoutsdrif Group. The Koras Group is petrologically similar to the Sinclair Sequence which is presently considered to be its coeval equivalent, but the dominantly calc-alkaline character of the Sinclair rocks distinguishes them from the dominantly tholeiitic Koras lavas. In a short literature review, the four main hypotheses for the petrogenesis of bimodal associations: liquid immiscibility, crystal fractionation, two-stage partial melting and separate magma sources, are described and the most feasible explanation for the origin of the Koras lavas is thought to be a "separate magma source" hypothesis in which two cycles of mantle-derived basalts and crustal-derived rhyolites were produced in a zone of high heat flow and erupted in an area of crustal weakness. The middle- or late-Proterozoic Koras Group was formed during unstable tectonic conditions, in a depositional setting that was probably controlled by late folding of the underlying pre-Koras sequences as well as the major strike-slip movement and subordinate dip-slip faulting in the Doornberg Lineament.
Keywords: Geology -- South Africa -- Cape of Good Hope